World Development Report 2000/2001 : Attacking Poverty - World Bank (New York: Oxford University Press, 2012)
This report focuses on the dimensions of poverty, and how to create a better world, free of poverty. The analysis explores the nature, and evolution of poverty, and its causes, to present a framework for action. The opportunity for expanding poor people's assets is addressed, arguing that major reductions in human deprivation are indeed possible, that economic growth, inequality, and poverty reduction, can be harnessed through economic integration, and technological change, dependent not only on the evolvement of markets, but on the choices for public action at the global, national, and local levels. Actions to facilitate empowerment include state institutional responsiveness in building social institutions which will improve well-being, and health, to allow increased income-earning potential, access to education, and eventual removal of social barriers. Security aspects are enhanced, by assessing risk management towards reducing vulnerability to economic crises, and natural disasters. The report expands on the dimensions of human deprivation, to include powerlessness and voicelessness, vulnerability and fear. International dimensions are explored, through global actions to fight poverty, analyzing global trade, capital flows, and how to reform development assistance to forge change in the livelihoods of the poor.